THE INFLUENCE OF SWIMMING LAYER AND SUB-SURFACE OCEANOGRAPHIC VARIABLES ON CATCH OF ALBACORE (Thunnus alalunga) IN EASTERN INDIAN OCEAN - fathur rochman; Widodo Setiyo Pranowo; Irwan Jatmiko (Indonesian Fisheries Research Journal, 2016)
The current study highlighted the relationship between the number of ALB catch, swimming layer and sub-surface oceanographic variables (temperature, dissolved oxygen, salinity, nitrate, phosphate and silicate) in Eastern Indian Ocean. This data used in this study were based on the Research Institute for Tuna Fisheries (RITF) observer program in Benoa from 2010-2013. This paper presents the information about vertical distribution of Albacore and its relations to sub surface oceanographic variables (SSOV). Results show that the optimum catch of albacore occurred at depth of 118 to 291 m with the average temperature between       12.41-20.47 °C, dissolved oxygen 3.24-4.68 ml/l , salinity 34.78-35.01 psu, nitrate 6.78-17.50 µ mol/l, phosphate 0.62-1.27 µ mol/l and  silicate 10.06-24.77 µ mol/l. The highest catches of albacore are mostly at depth of 156 m (hook number 2 and 11) with the average temperature 18.71°C, dissolved oxygen 4.68 ml/l, salinity 34.78 psu, nitrate 10.71 µ mol/l, phosphate 0.86 µ mol/l and silicate 15.95 µ mol/l. The highest influence of swimming layer and sub-surface oceanographic variable to the number of ALB catch contained at depth of 291 m of albacore swimming layer with coefficient correlation ( r ) 0.934 and determination coefficient ( R2) 0.872.  The lowest influence of  swimming layer and sub-surface oceanographic variable to the number of ALB catch  contained at depth of 156 m of albacore swimming layer with coefficient correlation ( r ) 0.528 and determination coefficient   ( R2) 0,279. The relationship between swimming layer and sub-surface oceanographic variable on catch of  ALB tuna was low (<0.500).